2008
DOI: 10.1159/000144101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an Effective Visual Field Testing Strategy for a Normal Pediatric Population

Abstract: Aim: To investigate which visual field testing strategy yields more reliable and tolerable field analysis in a normal pediatric population. Material and Methods: 68 healthy children aged 6–13 years with no ocular or systemic diseases were included in the study. One randomly selected eye of each child underwent standard achromatic visual field analysis using a Model 750 Humphrey Field Analyzer II (Carl Zeiss Meditec, Dublin, Calif., USA). We evaluated the reliability criteria (false negative, false positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…It is difficult to compare directly our kinetic data with the extant literature reporting VF size in children, because prior research involved assessments along fewer meridians, using large stimuli (V4e) only, 5,6 or had a small sample and analyzed with parametric methods. 20 However, visual inspection does show that our results in the oldest children are similar to the results of Egge 1 in 14-to 15-year-olds (n ¼ 68, Goldmann perimetry), albeit with a slightly smaller nasal field in our study, but similar confidence estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult to compare directly our kinetic data with the extant literature reporting VF size in children, because prior research involved assessments along fewer meridians, using large stimuli (V4e) only, 5,6 or had a small sample and analyzed with parametric methods. 20 However, visual inspection does show that our results in the oldest children are similar to the results of Egge 1 in 14-to 15-year-olds (n ¼ 68, Goldmann perimetry), albeit with a slightly smaller nasal field in our study, but similar confidence estimates.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The Goldmann perimeter is no longer available commercially, and only 1 study 7 has produced normative isopter area values in children using a kinetic perimeter with similar specifications, namely, the Octopus 900 (n ¼ 82; aged 5e15 years). Furthermore, the development of normative isopter models should account for the nonparametric distribution of points, yet current normative values (in adults and children) have failed to do this.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Aslam and colleagues 5 have recently described a computer game-based, child-friendly, flat-screen perimeter. 5 This system may be useful for detecting relative field deficit and scotomata in children but requires a learned and conscious response, which limits its use in younger and developmentally delayed children.…”
Section: Discussionmentioning
confidence: 99%
“…Akar et al [30] evaluated 68 6-to 13-year-old healthy children using Goldmann perimetry (V4 stimulus on 8 meridians at 3°/second). The testing took on average 11.06 minutes (11.06 ± 3.9 minutes), which was longer than in other comparable studies (shown in Table 1).…”
Section: Discussionmentioning
confidence: 99%